The European Union after the Lisbon Treaty - David Tonievich Karamanukyan (Сибирское юридическое обозрение, 2011)
The author analyzes the processes of modernization of the institutional structure and the functioning of the European Union under the Lisbon Treaty. Analysis of the provisions of the Lisbon Treaty held in comparison with the draft Constitution of the European Union in 2004 and the founding treaties.